Effect of rf power on the growth of silicon nanowires by hot-wire assisted plasma enhanced chemical vapor deposition (HW-PECVD) technique - Chong, S.K.; Goh, B.T.; Aspanut, Z.; Muhamad, M.R.; Dee, C.F.; Rahman, S.A. (2011)
Silicon nanowires (SiNWs) were synthesized by simultaneous evaporation of Au and Si deposition using H(2) diluted SiH(4). The deposition techniques combined hot-wire (HW) and plasma enhanced chemical vapor deposition (PECVD). Au wires were placed on the filament and heated simultaneously with the activation of the rf plasma for the dissociation of SiH4 and H2 gases. Five set of samples were deposited on ITO-coated glass substrate at different rf power varied from 20 to 100W in an interval of 20W, keeping other deposition parameters constant. High yield of SiNWs with diameter ranging from 60 to 400 nm and length about 10 mu m were grown at rf power of 80W (power density -1018 mW cm(-2)). Rf power of 100W (power density -1273 mW cm(-2)) suppressed the growth of these SiNWs. The growth mechanisms of SiNWs are tentatively proposed. The nanocrystalline structure of SiNWs is confirmed by Raman spectra and HRTEM measurement. (C) 2011 Elsevier B.V. All rights reserved.